Perancangan Aplikasi Trans Banyumas untuk Pariwisata Menggunakan Metode Agile Scrum - Nabil Hanif Pratama; Irma Barokah; Safira Anggraini Irawan; Muhammad Fauzan Yasykur (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2024)
Tourism in Banyumas Regency holds significant potential with a variety of attractive destinations, and to support tourist access, Trans Banyumas Bus serves as a public transportation mode. Accurate and easily accessible information is key to enhancing the tourist experience. Therefore, this research develops the Android application "TraBas Access," focusing on providing information about routes, stops, operational schedules, and tourist destinations in Banyumas. The application development applies the Scrum method, a part of the Agile framework chosen for its agility in responding to changes and providing transparency in the development process. Scrum's advantage, with its Sprints, enables the team to focus on specific features in each sprint phase, enhancing adaptability to changing needs. The developed system has undergone a series of Sprint Planning and testing using Black-Box testing, with results indicating the proper functionality of all application features.